Biodiversity literacy level of students in a senior high school - Anna Argiyanti; Kusnadi Kusnadi; Mimin Nurjhani K. (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Indonesia is one of the countries experiencing a decline in biodiversity due to climate change and human activities, whereas biodiversity has an important value to meet the basic needs of humans and other living things so it is very important to be preserved. Therefore, the awareness of each individual is needed to preserve biodiversity so that it remains sustainable so that the needs of life on earth remain stable. Knowledge that must be possessed by students on the topic of biodiversity include: the level of biodiversity, the role of biodiversity, actions that can reduce biodiversity and efforts to prevent and preserve biodiversity. Issues or problems about biodiversity need to be known and learned by students so that students are able to solve problems related to biodiversity in everyday life. Biodiversity literacy skills possessed by students are expected to be able to make a positive contribution in the community environment to maintain the sustainability of biodiversity in the future. Based on the above, the purpose of this study is to determine the level of biodiversity literacy of high school students. The population of this study were 70 high school students in class X semester 2 of the 2023-2024 school year. The technique of collecting data on the level of biodiversity literacy of high school students uses a multiple choice research instrument of 40 questions that refer to the World Wildlife Fund's biodiversity education framework. The results of the investigation showed the level of biodiversity literacy of high school students at the level of functional literacy, structural literacy and nominal literacy, but no students were found to have a level of biodiversity literacy in multidimensional literacy. So that learning is needed that can bring out and improve biodiversity literacy in students.Abstrak. Indonesia merupakan salah satu negara yang mengalami penurunan biodiversitas akibat perubahan iklim dan aktivitas manusia, padahal biodiversitas memiliki nilai penting untuk memenuhi kebutuhan dasar manusia dan makhluk hidup lainnya, sehingga sangat penting untuk dijaga kelestariannya. Karena itu diperlukan kesadaran setiap individu untuk menjaga kelestarian biodiversitas agar tetap lestari sehingga kebutuhan hidup di bumi tetap stabil. Pengetahuan yang harus dimiliki oleh mahasiswa pada topik biodiversitas antara lain: tingkat biodiversitas, peran biodiversitas, tindakan yang dapat mengurangi biodiversitas dan upaya pencegahan dan pelestarian biodiversitas. Isu-isu atau permasalahan tentang biodiversitas perlu diketahui dan dipelajari oleh siswa agar siswa mampu memecahkan masalah yang berkaitan dengan biodiversitas dalam kehidupan sehari-hari. Kemampuan literasi biodiversitas yang dimiliki oleh siswa diharapkan mampu memberikan kontribusi positif di lingkungan masyarakat untuk menjaga keberlangsungan biodiversitas di masa yang akan datang. Berdasarkan hal di atas, tujuan dari penelitian ini adalah untuk mengetahui tingkat literasi biodiversitas siswa SMA. Populasi penelitian ini adalah siswa SMA kelas X semester 2 tahun ajaran 2023-2024 sebanyak 70 orang. Teknik pengumpulan data tingkat literasi biodiversitas siswa SMA menggunakan instrumen penelitian pilihan ganda sebanyak 40 soal yang mengacu pada kerangka kerja pendidikan biodiversitas World Wildlife Fund. Hasil investigasi menunjukkan tingkat literasi biodiversitas siswa SMA pada tingkat literasi fungsional, literasi struktural dan literasi nominal, namun tidak ditemukan siswa yang memiliki tingkat literasi biodiversitas pada literasi multidimensional. Sehingga diperlukan pembelajaran yang dapat memunculkan dan meningkatkan literasi biodiversitas pada siswa.